Panorama dos repositórios digitais brasileiros de acesso aberto desenvolvidos com o software Tainacan - Tiago Silva de Carvalho (2022)
This work presents the current national scenario on open access digital libraries and repositories developed with Tainacan, an open-source Brazilian software used for digital collections management, developed by universities and other public agencies. Since its 2014 launch, hundreds of platforms, of the most wide-ranging themes, were developed using it. The research aimed to identify the national state of the art of these digital libraries and repositories created with Tainacan, as well as the investigation of their platform managers’ profiles. Therefore, the repositories structures were analyzed through a quantitative, exploratory, and applied research. This work’s steps encompassed literature review, followed by active and passive data gathering procedures. To make up the intentional sample, all active Brazilian open access repositories were selected from the “Use Cases” list available on the software’s website. The active data gathering was then realized upon the resulting 65 platforms, extracting diverse data from the collections, such as their theme or information architecture. On the other hand, the passive data gathering, carried out with a survey, had a participation rate of 57% institutions (or 37 in 65 repositories). Among the primary results, some of the highlights were: the major presence of public institutions, accounting for 83% of the sampled repositories; the prevalence of human and social sciences theme-related platforms; and the general definition of the managers’ profiles: composed mostly of white women, of ages between 30 and 39 years old, and masters (academic degree).